Surface temperature reconstructions for the last 2,000 years (National Academies Press, 2006)
In response to a request from Congress, Surface Temperature Reconstructions for the Last 2,000 Years assesses the state of scientific efforts to reconstruct surface temperature records for Earth during approximately the last 2,000 years and the implications of these efforts for our understanding of global climate change. Because widespread, reliable temperature records are available only for the last 150 years, scientists estimate temperatures in the more distant past by analyzing "proxy evidence," which includes tree rings, corals, ocean and lake sediments, cave deposits, ice cores, boreholes, and glaciers. Starting in the late 1990s, scientists began using sophisticated methods to combine proxy evidence from many different locations in an effort to estimate surface temperature changes during the last few hundred to few thousand years. This book is an important resource in helping to understand the intricacies of global climate change.